From Gulf to Bridge: When Do Moral Arguments Facilitate Political Influence?. (December 2015) - Feinberg, Matthew; Willer, Robb
Much of contemporary American political rhetoric is characterized by liberals and conservatives advancing arguments for the morality of their respective political positions. However, research suggests such moral rhetoric is largely ineffective for persuading those who do not already hold one's position because advocates advancing these arguments fail to account for the divergent moral commitments that undergird America's political divisions. Building on this, we hypothesize that (a) political advocates spontaneously make arguments grounded in their own moral values, not the values of those targeted for persuasion, and (b) political arguments reframed to appeal to the moral values of those holding the opposing political position are typically more effective. We find support for these claims across six studies involving diverse political issues, including same-sex marriage, universal health care, military spending, and adopting English as the nation's official langauge. Mediation and moderation analyses further indicated that reframed moral appeals were persuasive because they increased the apparent agreement between the political position and the targeted individuals' moral values.